2010
DOI: 10.1111/j.1749-6632.2010.05462.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of NKCC1 and KCC2 in the development of chronic neuropathic pain following spinal cord injury

Abstract: Neuropathic pain is a common problem following spinal cord injury (SCI). Effective analgesic therapy has been hampered by the lack of knowledge about the mechanisms underlying post-SCI neuropathic pain. Current evidence suggests GABAergic spinal nociceptive processing is a critical functional node in this complex phenotype, representing a potential target for therapeutic intervention. Normal GABA neurotransmission is dependent on precise regulation of the level of intracellular chloride, which is determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 27 publications
3
92
0
Order By: Relevance
“…KCC2 maintains the Cl 2 gradient by extruding Cl 2 from a cell, keeping a low intracellular Cl 2 concentration and thus an inhibitory Cl 2 current flowing through GABA A receptors. A number of studies have reported a significant downregulation of KCC2 and disruption of neuronal Cl 2 homeostasis in inflammatory and neuropathic pain models (Coull et al, 2003;Price et al, 2005;Miletic and Miletic, 2008;Zhang et al, 2008;Boulenguez et al, 2010;Hasbargen et al, 2010). All these findings of KCC2 downregulation were made in spinal dorsal horn neurons, so it is unclear whether a KCC2-mediated mechanism is involved in brain neurons and particularly in neurons in the brainstem descending pain-modulating system that maintains the pain hypersensitivity under chronic pain conditions (Porreca et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…KCC2 maintains the Cl 2 gradient by extruding Cl 2 from a cell, keeping a low intracellular Cl 2 concentration and thus an inhibitory Cl 2 current flowing through GABA A receptors. A number of studies have reported a significant downregulation of KCC2 and disruption of neuronal Cl 2 homeostasis in inflammatory and neuropathic pain models (Coull et al, 2003;Price et al, 2005;Miletic and Miletic, 2008;Zhang et al, 2008;Boulenguez et al, 2010;Hasbargen et al, 2010). All these findings of KCC2 downregulation were made in spinal dorsal horn neurons, so it is unclear whether a KCC2-mediated mechanism is involved in brain neurons and particularly in neurons in the brainstem descending pain-modulating system that maintains the pain hypersensitivity under chronic pain conditions (Porreca et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Authors have speculated, through various grant proposals, that by inhibiting upregulation of such pain molecules in the early phase and/or late phase of injury, spinal cord damage and induced NP could be ameliorated. Our research findings from previous studies have helped in understanding novel mechanisms and treatments for SCI and NP employing a rat model [36][37][38][39][40][41][42] . This review aims to prompt new studies that examine the possible relationship of nociceptive proteins and its implications in translational approach of yogic processes in NP.…”
Section: Understanding the Molecular Mechanisms Of Npmentioning
confidence: 99%
“…Taken together, these results indicate that NKCC1 is expressed in immature rodent white matter on developing OLs, as well as subplate and cortical neurons, during the peak period of susceptibility to PVL. As increases in NKCC1 expression following injury have been previously reported in epilepsy, stroke, chronic pain, and spinal cord injury (14,15,26,27), we then investigated whether NKCC1 expression on OLs and neurons changes following HI in the immature rodent. As in naive animals, immunostaining for NKCC1 in both P6 Long Evans rats and PLP-EGFP mice revealed NKCC1 on OLs and neurons in the hemisphere ipsilateral to ligation at 6 and 24 h post-HI ( Figure 5, n = 4/group).…”
Section: Nkcc1 Is Expressed On Developing Ols and Neurons In The Immamentioning
confidence: 99%
“…Gray matter injury 7 d post-HI (P13) was assessed as per our previously published methods (n = 7-9/group) (26). In brief, the extent of FluoroJade staining was compared in hemispheres ipsilateral and contralateral to the ligation in two sections per brain.…”
Section: Fluorjade-b Staining and Assessment Of Cell Deathmentioning
confidence: 99%